Application effect of the online and offline mixed education mode in nursing practice based on the SMCR communication model - Chen, Qian; Jin, Yanhong; Zhong, Lixia; Li, Yingying; Fu, Li; Zhang, Weiwei; Xu, Qiuying (Frontiers in Medicine, 2024)
Objective: To explore the application effect of online-offline mixed teaching method in nursing practice teaching based on SMCR communication model. Methods: By using convenience sampling method, 15 nursing students from April 1, 2022 to December 31, 2023 who practice their internship in the Department of Critical Care Medicine, Beijing Friendship Hospital Affiliated to Capital Medical University for 4 weeks were selected as the experimental group 16 nursing students who practiced in the same hospital in 2021 were selected as the control group. The control group used traditional teaching methods for teaching, and the experimental group used online and offline teaching methods for teaching. The theoretical and practical achievements, competency and teaching satisfaction of the two groups of nursing students were compared and analyzed after the internship. Results: The theoretical knowledge, operational performance, competence of the nurses and satisfaction with teaching of the experimental group were higher than those of the control group (P<0.05). Conclusion: Based on the SMCR communication model, exploring the online and offline mixed teaching method plays an important role in the teaching process of nursing practice, which can not only effectively improve the comprehensive performance of nursing students, but also help to improve their satisfaction with teaching, and has a positive impact on the cultivation of high-quality nursing talents.